Proceedings of the 20th International Workshop on Software and Compilers for Embedded Systems 2017
DOI: 10.1145/3078659.3078666
|View full text |Cite
|
Sign up to set email alerts
|

Data Dependent Energy Modeling for Worst Case Energy Consumption Analysis

Abstract: Safely meeting Worst Case Energy Consumption (WCEC) criteria requires accurate energy modeling of software. We investigate the impact of instruction operand values upon energy consumption in cacheless embedded processors. Existing instruction-level energy models typically use measurements from random input data, providing estimates unsuitable for safe WCEC analysis.We examine probabilistic energy distributions of instructions and propose a model for composing instruction sequences using distributions, enabling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In Ref. [18], 15% data-induced variation has been reported for the 8-bit AVR processor, while up to 1.7x data-dependent variation was observed for the 32-bit XMOS XCore in [19]. Variation of as much as 50% is reported in [19] for an ST20 32-bit microprocessor.…”
Section: The Impact Of Data On the Energy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [18], 15% data-induced variation has been reported for the 8-bit AVR processor, while up to 1.7x data-dependent variation was observed for the 32-bit XMOS XCore in [19]. Variation of as much as 50% is reported in [19] for an ST20 32-bit microprocessor.…”
Section: The Impact Of Data On the Energy Modelmentioning
confidence: 99%
“…[18], energy modelling for worst-case energy consumption analysis has been explored. The most promising approach uses probabilistic energy distributions to characterise individual instruction pairs and proposes techniques to compose these to block-level instruction sequences.…”
Section: The Impact Of Data On the Energy Modelmentioning
confidence: 99%
“…The profiling framework executes tightly coupled threads through the xCORE pipeline, with random, valid operand values to produce an average power estimate for each instruction. Random input data is shown to cause higher power dissipation than more constrained data that would be found in real-world programs [19], e.g. due to data dependencies, thus creating a modest over-estimate in most cases.…”
Section: Defining and Constructing An Energy Modelmentioning
confidence: 99%
“…We demonstrated that the variation due to data can range from 5 to 25% [8]. In [19] we examine the impact of operand values on instruction level energy consumption and propose a probabilistic approach to developing worstcase energy models suitable for safe worst-case energy consumption analysis.…”
Section: Software Energy Modelling Challengesmentioning
confidence: 99%
“…In research, the wands have been used to collect energy data for processor and communication modelling [7], data-dependent energy modelling [8,9] and exploration of compiler optimizations for energy efficiency. Finally, the MAGEEC wand was of course pivotal in the research output of the MAGEEC energy efficient compiler optimization research.…”
mentioning
confidence: 99%